KECEMASAN MENGHAMBAT ONSET LAKTASI IBU POST PARTUM - Rizki Lia Puspita; Ida Nursanti (MEDIA ILMU KESEHATAN, 2013)
Background: Lactation is the overall process of breastfeeding production until the baby suckling. Exclusive breastfeeding has many benefits for mother and the baby, it is supported by UNICEF and WHO with Baby friendly Hospital Initiative program. However, exclusive breastfeeding rates remain low. Some studies show that delayed onset of lactation are less likely to continue full breastfedding. One factor that may influence the delayed onset of lactation is anxiety levels in the postpartum. Purpose: To knew how the relationship between the anxiety levels with onset lactation postpartum mothers in RSUD Panembahan Senopati Bantul. Methods: The study used cohort prospective to 60 respondents were recruited with purposive sampling. Analysis of the data devided be univariable and bivariabel analysis using chi-square with a significance level of p <0.05. Results: There was a significant association between levels of anxiety with the onset of lactation on postpartum mothers. Mothers who experienced mild levels of anxiety most rapid onset of lactation 81.7%, and mothers with severe levels of anxiety experienced were delayed onset of lactation (p = 0.000). Conclusion: The level of anxiety in postpartum influence to delayed onset of lactation. Suggestion: Good preparation for pregnancy and family support may affect on anxiety levels in postpartum. Keywords: Levels of anxiety, Onset Lactation